Pengaruh Kemampuan Komunikasi dan Budaya Organisasi Terhadap Efektivitas Kerja Karyawan pada PT. Interskala Sehat Sejahtera - Sinta Fauziah; Roy Irawan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Human resource issues are still in the spotlight and the focus for companies to survive in the era of globalization. This research uses primary data, namely data obtained directly from the field by distributing questionnaires specifically to employees to obtain 60 respondents. From the results of multiple linear regression analysis, the multiple regression equation is obtained as follows: Y= 17.484 + 0.460 X1 + 0.185 This research uses theory as a basis for field exploration. This research approach uses quantitative methods. Research findings show that the Fcount value (6.882) > the Ftable value (3.159) and the significant value is 0.002 < the significance level (0.05). Ha is accepted and Ho is rejected, therefore it can be concluded that the variables of communication skills and organizational culture simultaneously influence the effectiveness of employee performance. Based on the research results, the variables (communication skills and organizational culture) influence the dependent variable (employee work effectiveness) by 19% and the remaining 81% is influenced by other variables outside this research. The respondents of this research are employees of PT. Interskala Sehat Sejahtera, this research was conducted to see the influence of communication skills and organizational culture on employee work effectiveness at PT. Health and Prosperity Interscale